The psychological impact of Early Pregnancy Loss in Portugal: incidence and the effect on psychological morbidity - Mendes, Diana C. Gonçalves; Fonseca, Ana; Cameirão, Mónica S. (Frontiers in Public Health, 2023)
Introduction: Worldwide, up to a quarter of all recognized pregnancies result in Early Pregnancy Loss (EPL), also known as miscarriage. For many women, this is a traumatic experience that leads to persistent negative mental health responses. The most common morbidity reported in studies from different countries is complicated grief, usually comorbid with depression, anxiety and Post-Traumatic Stress Disorder (PTSD). To our best knowledge, no studies characterizing the psychological impact of EPL have been made in Portugal. Methods: An online survey was conducted to evaluate clinical symptoms of perinatal grief, anxiety, depression, and PTSD in women who suffered a spontaneous loss within 20 weeks of gestation. Out of 1015 women who answered this survey, 873 were considered eligible and subsequently distributed into 7 groups according to the time passed between their loss and their participation in the study. Results: The proportion of women showing symptoms of all comorbidities was greater in those whose loss had happened within a month, and there was a significant gradual decrease over time in the proportions of clinical perinatal grief and PTSD. In terms of depression symptoms, proportions dropped significantly in the group whose loss occurred 2-3 months before their participation but oscillated without great changes in the groups representing older losses. Regarding anxiety, there were small oscillations, but there was no significant decrease in symptoms over time. Discussion: Overall, despite a general drop in proportions for most morbidities over time, substantial proportions of women showed persistent symptoms of clinical morbidities three years or more after the loss. Therefore, it is essential to promote monitoring of possible complicated responses to the event, to provide appropriate and timely intervention to those women in need.